Enhanced interfacial characteristics of perovskite solar cell with multi-functional organic hole-selective interlayer. (January 2022) - Park, Hansol; Kye, Hyojin; Jeong, Bum Ho; Heo, Jihyeon; Hwang, Sooji; Kim, Bong-Gi; Park, Hui Joon
Abstract: In solution-processed organic and inorganic halide perovskite solar cells (PSCs), managing the interfacial characteristics between multi-layers has been a crucial factor in determining their performance and stability. Here, we newly design an indolocarbazole-based organic molecule that can enhance the interfacial properties between a solution-processed NiOx hole transport layer and perovskite in p-i-n planar PSC. Especially, to be beneficial to this architecture, its visible transparency and energy level are optimized, and its chemical structure is crosslinked for better solution processability as a hole-selective interlayer. More importantly, it can passivate the defects in the perovskite film, consequently enhancing the quality of the film and suppressing non-radiative recombination in the devices. With this interface modification, we confirm that the performance and stability of PSC devices are largely enhanced. Highlights: An indolocarbazole-based organic hole-selective interlayer is newly synthesized. Its chemical structure is crosslinked for better solution processability. This is added to the interface between NiOx and perovskite of p-i-n PV. This modifies hydrophobicity of NiOx and passivates defects at the interface. The efficiency increases from 16.1% to 18.2%, with over 500 h stability in air.